Psychopharmacology - Robbins, Trevor W.; Miczek, Klaus A.; Hoyer, Daniel; de Wit, Harriet; Curran, Valerie H.; Price, Lawrence H.; Morrow, A. Leslie; Baunez, Christelle; Lucki, Irwin; Hashimoto, Kenji; D'Souza, Deepak; Floresco, Stan B.; et al. (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Psychopharmacology is an international journal of research and scholarship, the aims of which are to cover the general area of elucidating the neurochemical mechanisms that affect behavior, all terms understood in the broadest sense. The scope of the Journal extends from clinical psychopharmacology (including trials), to experimental studies on the effects of drugs on cognition and behavior in humans and laboratory studies in experimental animals. The research methodologies (techniques covered) may range from neurochemical assays and electrophysiological recording to studies of functional neuroimaging, and the methods of experimental psychology and ethology, as well as clinical neurology and psychiatry. The journal is particularly interested in articles that integrate these levels of analysis.
Keywords: Neurosciences; Pharmacology; Psychiatry; Neurosciences; Pharmacology/Toxicology.; Psychiatry